Aplikasi Pembelajaran Interaktif pada Mata Pelajaran Informatika Berbasis Android - Retnoningsih, Dwi; Hari Saputro Al Haris, Firdhaus; Charolina, Astri; Mandansari, Titik (Jurnal Algoritma, 2025)
Active, innovative, and enjoyable learning has become a necessity today. SMK Muhammadiyah 5 Miri Sragen is a school committed to implementing active and innovative learning. However, limited computer laboratory facilities have prevented the optimal implementation of Informatics learning. Additionally, students still use smartphones more for entertainment than for learning. This study aims to design and develop an interactive Android-based learning application in accordance with the Merdeka Curriculum. This application is intended for 10th grade students from all majors and features learning materials, instructional videos, discussion forums, and interactive quizzes. The development method used is ADDIE, while data collection is carried out through observation, interviews, and literature studies. The results of testing using the black box method on 15 scenarios show that all features work as expected. In addition, beta testing involving 104 respondents resulted in a satisfaction rate of 78.8%, which is considered acceptable. This application has been proven to improve students' understanding of computer science in an interactive and flexible manner. This application also contributes to improving the efficiency of teachers in processing student grades. For schools, it provides benefits in the form of improved quality of digital learning.